Searching for place : Ukrainian displaced persons, Canada, and the migration of memory - Luciuk, Lubomyr Y., 1953- (Toronto, Ont. : University of Toronto Press, 2000)
"Canada was not in a welcoming mood when Ukrainian Displaced Persons and other refugees began immigrating after the Second World War. In this documented account, Lubomyr Y. Luciuk maps the established Ukrainian Canadian community's efforts to rescue and resettle refugees, despite public indifference and the hostility of political opponents in Canada and abroad. He explores the often divisive impact that this 'third wave' of nationalistic refugees had on organized Ukrainian Canadian society, and traces how this diaspora's experiences of persecution under the Soviet and Nazi regimes in occupied Ukraine, and their subsequent hiving together in the cauldrons of the postwar DP camps, underlay the shaping of a shared political world-view that would not abate, despite decades in exile. Drawing on personal diaries, in-depth interviews, and previously unmined government archives, the author provides an interpretation of the Ukrainian experience in Canada that is both illuminating and controversial, scholarly and intimate. Luciuk reveals how a distinct Ukrainian Canadian identity emerged and has been manipulated, negotiated, and recast from the beginnings of Ukrainian pioneer settlement at the turn of the last century to the present. Searching for Place represents a provocative contribution to the study of modern Canada and one of its most important communities."--Jacket
Mn -- o -- p -- q -- r -- s -- t -- u -- v -- w -- y -- z -- illustrations
Includes bibliographical references (pages 500-524) and index.
Print version record.
JSTOR
Keywords: Ukrainians -- Canada -- History -- 20th century; Refugees -- Ukraine -- History -- 20th century; Refugees -- Government policy -- Canada; Ukrainians -- Canada -- Attitudes -- History -- 20th century; Ukrainian Canadians -- History; Ukrainian Canadians -- Attitudes; Canadiens d'origine ukrainienne -- Histoire -- 20e siècle.; Ukrainiens -- Canada -- Histoire -- 20e siècle.; Ukrainiens -- Canada -- Attitudes -- Histoire -- 20e siècle.; Réfugiés -- Ukraine -- Histoire -- 20e siècle.; Réfugiés -- Politique gouvernementale -- Canada; HISTORY -- Canada -- General; Refugees; Refugees -- Government policy; Ukrainians; Canada; Ukraine; 1900-1999; Electronic books; e-books.; History; Livres numériques.